1999
DOI: 10.1164/ajrccm.159.5.9806044
|View full text |Cite
|
Sign up to set email alerts
|

Number and Proliferation of Clara Cells in Normal Human Airway Epithelium

Abstract: Experimental pathologic studies suggest that Clara cells are one of the types of airway stem cells but the proliferation of Clara cells in human lungs has not yet been examined. The purpose of this study was to assess in conducting airways of normal human lungs: (1) the number of Clara cells; and (2) the contribution of Clara cells to the proliferation compartment. Samples of histologic normal tissue were taken from seven lungs obtained by autopsy. A triple sequential (immuno)histochemical staining was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
228
2
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(250 citation statements)
references
References 19 publications
17
228
2
3
Order By: Relevance
“…As in proximal airways, the CFTR immunostaining signal was clear and consistent in the apical PM of every ciliated cell of the bronchiolar epithelium (7 normal subjects, Figure 6A). CFTR was not detected in Clara cells (note, Clara cells were absent in the human proximal bronchioles as previously reported by Boers et al 1999), nor in the PM of goblet cells identified with MUC5AC antibodies ( Figure 6B). …”
Section: Cftr Immunolocalization In Small Airwayssupporting
confidence: 80%
“…As in proximal airways, the CFTR immunostaining signal was clear and consistent in the apical PM of every ciliated cell of the bronchiolar epithelium (7 normal subjects, Figure 6A). CFTR was not detected in Clara cells (note, Clara cells were absent in the human proximal bronchioles as previously reported by Boers et al 1999), nor in the PM of goblet cells identified with MUC5AC antibodies ( Figure 6B). …”
Section: Cftr Immunolocalization In Small Airwayssupporting
confidence: 80%
“…Function of the respiratory epithelium also relies upon Clara and goblet cells to secrete proteins that maintain the function of the periciliary layer (46,47). Goblet cells are glandular columnar cells more localized in bronchi that secrete mucin; MUC5A/C is the gene that encodes Mucin 5AC and is associated with goblet cells in the respiratory epithelium (48).…”
Section: Resultsmentioning
confidence: 99%
“…5C). The relative distribution of these Clara cells is representative of in vivo airways where they represent 0.4% of cells in the trachea, increasing up to 22% in the bronchioles (46). Goblet-cell distribution is <2% in the large airways of mice but is often higher in human airways, dependent upon exposure to environmental factors.…”
Section: Resultsmentioning
confidence: 99%
“…Third, in pathogen-free rats, the total number of airway epithelial cells remains constant during TGF-␣-induced goblet cell production, whereas the number of Clara cells decreases, suggesting that goblet cells form via differentiation of Clara cells (61). Indeed, some Clara cells can serve as stem cells (16,22), and some airway epithelial cells express both Clara cell secretory protein and mucin (5,14,25), suggesting that Clara cells are goblet cell precursors. However, whether goblet cells arise via cell differentiation has been questioned recently.…”
Section: Discussionmentioning
confidence: 98%
“…This evidence derives from several sources. First, goblet cells show no evidence of DNA synthesis (5,18,66) and contain unphosphorylated retinoblastoma protein and decreased levels of cyclin D 1 and cyclin-dependent kinase 2 (10), consistent with cell cycle arrest in the G1 phase. Second, in the endotoxin-treated rat nose, goblet cell production proceeds in the presence of metaphase blockade, indicating that goblet cell metaplasia can occur in the absence of cell proliferation (53).…”
Section: Discussionmentioning
confidence: 99%